2020
DOI: 10.1155/2020/8844219
|View full text |Cite
|
Sign up to set email alerts
|

Central Sensitivity Is Associated with Poor Recovery of Pain: Prediction, Cluster, and Decision Tree Analyses

Abstract: The process of pain recovery varies and can include the recovery, maintenance, or worsening of symptoms. Many cases of patients with pain show a tendency of recovering as predicted; however, some do not. The characteristics of cases that do not fit the prediction of pain recovery remain unclear. We performed cluster and decision tree analyses to reveal the characteristics in cases that do not fit the prediction of pain recovery. A total of 43 patients with musculoskeletal pain (nonoperative: 22 patients, opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Third, this study could only examine the longitudinal course of CSS for one month. Some studies can assume that changes in CSS occur for one month 13 . Still, since some studies have found intervention effects over extended periods (3 or 6 months) 27 Therefore, the low number of participants who changed the group classification might be related to the short follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, this study could only examine the longitudinal course of CSS for one month. Some studies can assume that changes in CSS occur for one month 13 . Still, since some studies have found intervention effects over extended periods (3 or 6 months) 27 Therefore, the low number of participants who changed the group classification might be related to the short follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…CSI has been shown to be associated with pain severity 11 , and higher CSI scores have been reported to have a poorer prognosis 12 . The CSI score is important not only for the initial score but also for monitoring the amount of change, which is related to the prognostic value of pain 13 . However, CSI is not necessarily associated with pain severity, and there is a subgroup of patients with low pain but severe CSI 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Tese results may indicate that the factors leading to chronicity are more infuenced by body perception disturbance than by the disease duration itself. Tus, these factors may be used to predict chronicity [28].…”
Section: Multiple Regression Analysis For Body Perceptionmentioning
confidence: 99%
“…CSSs are an essential factor of pain that have been reported to mediate the relationship between psychological factors and pain [ 13 ]. In addition, patients with pain who do not show improvement in CSSs tend not to show improvement in pain [ 14 ]. Interestingly, CSSs have been reported as an independent factor associated with a substantially lower rate of work retention [ 15 ].…”
Section: Introductionmentioning
confidence: 99%